2005
DOI: 10.1038/sj.npp.1300710
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Chronic Exposure to Antipsychotic Medications on Brain Size before and after Tissue Fixation: A Comparison of Haloperidol and Olanzapine in Macaque Monkeys

Abstract: It is unclear to what degree antipsychotic therapy confounds longitudinal imaging studies and post-mortem studies of subjects with schizophrenia. To investigate this problem, we developed a non-human primate model of chronic antipsychotic exposure. Three groups of six macaque monkeys each were exposed to oral haloperidol, olanzapine or sham for a 17-27 month period. The resulting plasma drug levels were comparable to those seen in subjects with schizophrenia treated with these medications. After the exposure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
250
3
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(270 citation statements)
references
References 72 publications
13
250
3
2
Order By: Relevance
“…34 The expression patterns of GAD 67 , SST and GABA A a1 mRNAs, as revealed by in situ hybridization, did not differ across the groups of monkeys ( Figure 6). One-way ANOVA confirmed the absence of an effect of drug exposure on the expression levels of GAD 67 Because substances such as alcohol, benzodiazepines or valproic acid affect GABA neurotransmission, we assessed whether the usage of these substances by subjects with schizophrenia at the time of death had any effect on the expression changes of the 10 GABA-related transcripts revealed by microarray.…”
Section: Relationship Among Transcript Expression Changesmentioning
confidence: 91%
See 2 more Smart Citations
“…34 The expression patterns of GAD 67 , SST and GABA A a1 mRNAs, as revealed by in situ hybridization, did not differ across the groups of monkeys ( Figure 6). One-way ANOVA confirmed the absence of an effect of drug exposure on the expression levels of GAD 67 Because substances such as alcohol, benzodiazepines or valproic acid affect GABA neurotransmission, we assessed whether the usage of these substances by subjects with schizophrenia at the time of death had any effect on the expression changes of the 10 GABA-related transcripts revealed by microarray.…”
Section: Relationship Among Transcript Expression Changesmentioning
confidence: 91%
“…Antipsychotic-exposed monkeys As described previously, 34 experimentally naive, male macaque monkeys (Macaca fasicularis) (LABS of Virginia, Yemassee, SC, USA), 4.5-5.3 years of age, were chronically exposed to twice daily oral doses of haloperidol, olanzapine or placebo (n = 6 monkeys per group) for 17-27 months. The doses of haloperidol and olanzapine were gradually increased until the monkeys were receiving 24-28 mg of haloperidol or 11.0-13.2 mg of olanzapine per day.…”
Section: Real-time Qpcrmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Since most antipsychotic compounds affect the levels of these and other neurotransmitters, the effect of specific transmitter systems on white matter integrity is challenging to disentangle. Preclinical 15 and clinical studies 16 have reported subtle white matter reductions after antipsychotic exposure. Haloperidol may downregulate genes associated with myelin and oligodendrocyte function.…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotic administration has been reported to be associated with changes in GM volumes in humans (24,25) and GM and WM reductions in nonhuman primates (29). Moreover, mood stabilizers such as lithium and valproate may increase GM volume (30,31).…”
mentioning
confidence: 99%